The Analysis Of Safe Clinical Services Indicators Of Tehran University Of Medical Sciences Selected Hospitals - Zhila Najafpour; Abolghasem Pourreza (Tehran University of Medical Sciences, 2016)
Background and Aim: The analysis of patients' safety clinical indicators is considered as one of the safety improvement instruments. Therefore, the present study is aimed to analyze the indices of safety clinical services in selected hospitals of Tehran University of Medical Sciences (TUMS). Materials and Methods: The present descriptive-analytical study was conducted in 11 TUMS hospitals in 2013. The study tool was the patient safety evaluation protocol of the World Health Organization (WHO). A checklist was completed following interviews, observations, and documentation reviews. The data were analyzed with descriptive and analytical tests, and SPSS software version 13. Results: The average scores of the studied hospitals were 96.6, 85.6 and 66 for the required, basic and advanced indices, respectively. The figure was not acceptable in required standards, but it was acceptable in basic and advanced ones. In the studied hospitals, numbers 7, 2, 4, 11, and 9 enjoyed the highest amount of conformity with standard, and were placed in rank 2 according to the ranking protocol. Finally, there was no meaningful statistical difference among hospitals in their observance of standards. Conclusion: Conformity with necessary standards was low in 6 studied hospitals, but in 5 hospitals, it was acceptable in basic and advanced standards. Hospitals need enhancement programs in statements of information management system, drugs management system, infection reduction system, and effective clinical system.